Optimal investment-reinsurance strategy on dynamic mean-variance problem with stochastic volatility - Sun, Jingya (Nanyang Technological University, 2021)
In this final year project, we further study the dynamic mean-variance problem with constrained risk control on reinsurance and investment (no-shorting) strategy for insurers with unknown expected terminal wealth. This project will fi rst solve the problem under traditional Black-Scholes model, where the problem is first embedded into an auxiliary stochastic linear-quadratic (LQ) control problem. Then a viscosity solution of Hamilton-Jacobi-Bellman (HJB) equations is identifi ed so as to derive the e fficient frontier and e fficient strategies explicitly by a verfi cation theorem. An extension on solving the problem under the stochastic volatility model will be studied as well.